How to get the most out of the ERS International Congress 2021 and an overview of the Early Career Member session - Farr, Amy (2021)
The annual European Respiratory Society (ERS) International Congress will take place in a virtual format, from 5 to 8 September 2021. As in previous years, the programme will be full of outstanding scientific sessions in the field of respiratory medicine and enriching opportunities for Early Career Members (ECMs). In this article, we provide an overview of the structure and content of the Congress, as well as tips on how to navigate the programme and get the most out of it. We also provide a brief description of the ECM session which will focus on the keys to success in science.